Analisis Implementasi Kode Etik Profesi Auditor atas Seksi 110 Prinsip Dasar Etika IAPI - Dewi Cahya Ningsih; Ayatulloh Michael Musyaffi; Tri Hesti Utaminingtyas (Indo Publishing, 2026)
This study aims to analyze the application of the basic principles of auditor ethics in Section 110 of the IAPI Code of Ethics at KAP XYZ & Partners, the challenges in its implementation, as well as the roles of IAPI and P2PK in fostering and supervising ethical compliance. This study employs a qualitative approach using the case study method. The results indicate that: (a) The application of the five ethical principles (integrity, objectivity, competence, confidentiality, and professional conduct) is well-established and integrated into audit procedures; (b) Major challenges include client pressure, threats to independence, time constraints, and audit cost dilemmas; (c) IAPI conducts supervision and guidance through mandatory PPL, quality reviews, and tiered sanctions; (d) P2PK performs risk-based supervision in accordance with PMK No. 186/2021 through client reporting requirements, periodic inspections, and the imposition of administrative sanctions. This study is limited to involving only partners and senior auditors as informants, so the perspectives from mid-level management such as supervisors or audit managers have not been explored. In addition, the focus of this study is only on Section 110 of KEPAP 2021, without examining other sections that are relevant to the challenges found in the field. Future research is suggested to expand the scope by involving various levels of positions within public accounting firms, as well as examining other sections in KEPAP 2021.